Penerapan Customer Relationship Management (CRM) pada Sistem Informasi Penjualan Bucket Berbasis Web di Toko Hadinafa Galery - Nila Indasari; Seni Asria; Muhammad Fauzi Razak; Nurmadina Hs (Ikatan Ahli Informatika Indonesia, 2023)
A web-based bucket sales information system with the implementation of Customer Relationship Management (CRM) is urgently needed in selling buckets at the Hadinafa Gallery store. This study aims to: (1) Build a web-based bucket sales information system by implementing Customer Relationship Management (CRM) at the Hadinafa Gallery store, (2) Implement a web-based bucket sales information system by implementing Customer Relationship Management (CRM) at te Hadinafa Gallery store. System activity design uses UML (Unified Modelling Language) which consists of 4: Use case diagram, Sequence diagram, Activity diagram, and Class diagrams. The programming languages used are PHP (PHP Hypertext Processor), MySQL, and Codeigniter4. Data collection was carried out in 3 ways, namely observation, interviews and library techniques. The results of this research are to make it easier for store owners to manage sales report data, customer data, and product data and help customers get bucket information without coming directly to the store.